Android development with Flash your visual blueprint for developing mobile apps - Dolce, Julian (Indianapolis, IN : Wiley Pub., 2010)
Presents instructions for creating Android applications using Flash, with information on such topics as downloading the Android SDK, compiling from the command line, building images, working with data from SQLite databases, and using URL protocols.
Includes index.
All age.
Keywords: Android (Electronic resource); Flash (Computer file); Android (Electronic resource); Flash (Computer software); Application software -- Development; Mobile computing; Application software -- Design